Growth rate and resource imbalance interactively control biomass stoichiometry and elemental quotas of aquatic bacteria. Issue 3 (March 2017) - Godwin, Casey M.; Whitaker, Emily A.; Cotner, James B.
Abstract: The effects of resource stoichiometry and growth rate on the elemental composition of biomass have been examined in a wide variety of organisms, but the interaction among these effects is often overlooked. To determine how growth rate and resource imbalance affect bacterial carbon (C): nitrogen (N): phosphorus (P) stoichiometry and elemental content, we cultured two strains of aquatic heterotrophic bacteria in chemostats at a range of dilution rates and P supply levels (C:P of 100:1 to 10, 000:1). When growing below 50% of their maximum growth rate, P availability and dilution rate had strong interactive effects on biomass C:N:P, elemental quotas, cell size, respiration rate, and growth efficiency. In contrast, at faster growth rates, biomass stoichiometry was strongly homeostatic in both strains (C:N:P of 70:13:1 and 73:14:1) and elemental quotas of C, N, and P were tightly coupled (but not constant). Respiration and cell size increased with both growth rate and P limitation, and P limitation induced C accumulation and excess respiration. These results show that bacterial biomass stoichiometry is relatively constrained when all resources are abundant and growth rates are high, but at low growth rates resource imbalance is relatively more important than growth rate in controlling bacterial biomass composition.